INSTAGRAM’S SHIFT TOWARDS LIVE: HOW STORIES AND LIVE VIDEOS SHAPE HOW WE EXPERIENCE BEING AT EVENTS - Hammelburg, Esther (AoIR Selected Papers of Internet Research, 2023)
Instagram has long been about sharing perfect pictures. For their Instagram posts many users beautify scenes from everyday life, elevate photogenic aspects, and articulate special moments in a style that fits the standards of Instagram culture (Leaver et al., 2020; Manovich, 2017). The term “instagrammable” found its way into many dictionaries and is widely used as a promotional label, for instance in tourism, food, and the museum sector. However, since the introduction of Instagram Stories and Instagram Live – in 2016 – an increasingly large part of the content shared on Instagram is no longer instagrammable in the same sense. These features afford instantaneous sharing of images and videos that are not necessarily displayed permanently, introducing a very different visual language and new visual practices. At festivals, Instagram is a ubiquitous platform. Many event-goers share their live experiences through posts and stories, often using event-specific hashtags, locations, and stickers. Based on an elaborate empirical examination of event-goers’ Instagram practices, this paper argues that Instagram’s shift towards live shapes their live experiences in distinct ways.